(untitled) (The Review of Diabetic Studies, 2025)
Background: Medication reconciliation is an important patient safety practice in the intensive care unit (ICU), where transfer of care increases the likelihood of discrepancies. International evidence highlights the clinical importance of addressing these differences to avoid preventable adverse events (ADE). This study enriches global literature by stating from a tertiary care hospital in Madina, Saudi Arabia and is part of the continuous quality improvement program in collaboration with Vision 2030 goals. To assess the prevalence, patterns and factors associated with medication discrepancies among ICU admitted patients in a tertiary hospital in Madina. Methods and Materials: A retrospective observational cohort study was performed with 134 adult ICU survivors discharged in the year 2024/2025. Discrepancies between pre-admission medications and prescriptions at ICU discharge were categorized into six types: medication omitted, duplicated, prescribed at the wrong dose, prescribed through an inappropriate route of administration, continued for the wrong duration or no longer indicated. The main outcome was description of discrepancies; second analyses of factors risking. Statistical analyses were conducted using descriptive frequencies, chi-square/Fisher’s exact tests, and multivariable logistic regression analysis and significance was taken as p<0.05.Results:Seventy (52.2%) patients were found to have at least one medication discrepancy. Among the types, omission of drugs and changes in dosage were the most frequently observed. Polypharmacy (or ≥5) emerged as a strong correlate of discrepancies in univariate analysis (all commercials had p<0.001), and was the only independent predictor identified on multivariable modeling (OR ≈ 5.8; 95% CI = [1.8, 18.9]; p=0.0037). Other comorbidities, such as cardiovascular disease and pulmonary disease were associated in univariate analyses but lacked independence. Conclusion: Medication discrepancies were commonly observed in discharges from the ICU with polypharmacy as the most important independent predictor. These occur emphasize the need for formal reconciliation process, especially in patients with polypharmacy to improve patient safety and care continuity that meet international standards as prescribed by Vision 2030.